2. On Beryllite and Bertrandite from Ilímaussaq Alkaline Intrusion, South Greenland. - Andersen, Steen (Meddelelser om Grønland, 1967)
The two beryllium silicates beryllite and bertrandite and their mode of occurrence are described from the Ilimaussaq alkaline intrusion. Optical and X-ray data are presented for the two minerals together with chemical analyses of two beryllite samples. The data for bertrandite correspond closely to those given for bertrandite from other localities. The identification of the beryllite is based on the similarity in X-ray data with the Lovozero type mineral. Pronounced differences from the latter are found in the refractive indices which are 1.50 < n < 1.52, and in the water content which varies in different samples from Ilimaussaq. The two minerals are associated with the beryllium minerals epididymite, eudidymite, chkalovite and sorensenite. The beryllium minerals are found in analcite veins and pockets formed in a late stage of the development of the complex. It is argued that differences in the partial water pressure of hydrothermal fluids govern the formation of the two minerals.